La ruta de la empanada: análisis de los aspectos comunicativos en la práctica de la cocina ecuatoriana tradicional y en la elaboración de la empanada de viento. - Mora Pichucho, Marcela Alexandra (2015)
The Ecuadorian culture as the basis of current cultural processes set of intangible way the current worldview; however, globalizing communicative practices whose center is the indispensable use of information technology and communication, as reported in the art of transmedia only, have been relegated to traditional practices making them part of cultural history, weakening the emphasis of traditional communicative praxis in particular customs of Ecuador, as in the case of the communicative process of making food. Becoming latter is an aspect of everyday life of the peoples in their practice is mainly characterized by its cultural, historical and religious background. Communication from epistemology is agreed with the socio-cultural nature of traditional cuisine to reconfigure meanings related to the usual practice in the field of communication and its various symbiotic and different levels of seniority systems. Specifically, the Ecuadorian cuisine enjoys a broad cultural mix, considering the vast ideological and empirical influences that has collected and naturalized in relation to products and practices collected from other cultures at international and intercontinental level, and even mixtures produced within the territory. So that messages are created in the practice of traditional cuisine, whether abstract and undocumented, have a great cultural weight and an invaluable heritage. Such is the case of the development of traditional pie wind, the same as, besides having an invaluable ethnographic value is the result of social situations and relationships times of cultural formation of the country, including the determination of social stratifications and elitist scenarios whose impacts are true today.